Project-Based Learning (PjBl) Green Pedagogy E-Module in Improving Creative Thinking and Digital Literacy - Wahyuni, Resma; Firdaus LN, Firdaus LN; Putra, Riki Apriyandi; Linggasari, Mariani Natalina; Wulandari, Putri Adita; Fadilah, Mellani (FKIP - Universitas Riau, 2025)
The PjBL learning model needs to be outlined in a learning module to help learning be more interesting and effective. During the two years of the implementation of the green pedagogy course, there has been no PjBL-based learning module that can be used by students. This research aims to produce PjBL-based e-modules to improve the effectiveness of green pedagogy learning. This research is a Research and Development (R&D) research using the ADDIE model, with development steps namely; Analysis, Design, Development, Implementation, and Evaluation. The research sample is 30 students who are taking green pedagogy courses. The research instrument consisted of a validation sheet with descriptive data analysis techniques. The module feasibility testing stage is carried out by product validation by two experts. Based on the results of the study, it was concluded that PjBL-based e-modules are very valid and can be used in the learning process.